Does GP practice size matter? GP practice size and the quality of primary care - Elaine Kelly; George Stoye (Institute for Fiscal Studies (IFS), 2014)
This report examines trends in the organisation of general practitioner (GP) practices in England between 2004 and 2010, and the relationship between practice size and two indicators of the quality of care: Quality and Outcomes Framework (QOF) scores; emergency in patient admissions for ambulatory care sensitive (ACS) conditions. We also examine the relationship between practice size and outpatient referral behaviour. There has been a substantial change in the organisation of GP practices overtime. There has been an increase in the average number of full-time equivalent (FTE) GPs in each practice, which rose from 3.6 in 2004 to 4.2 in 2010. The share of single-handed GP practices fell by a third, from 22% to15% over this period. These changes have resulted in a shift of registered patients towards larger practices. By 2010, 76% of those who were registered with a GP practice were registered with one that had more than three FTE GPs. This compares with a figure of 69% in 2004. Using data from 2010/11, all three indicators of quality that we examined show that smaller practices are associated with poorer quality in primary care services. The precise nature and size of this relationship vary across the different measures. There is a small, positive association between QOF scores and practice size. Single-handed practices have the lowest average (mean) QOF scores, while large practices (with more than six FTE GPs) achieve the highest average scores. For ACS admissions, there is some evidence that smaller practices perform worse, on average, than larger practices and are more likely to be among the worst performing. This precise relationship differs across different conditions. Across all the conditions studied, practices with more than six FTE GPs have lower admission rates on average than smaller practices. In the case of chronic conditions, single-handed practices are most likely to be among the poorest-performing practices. Practices with three or fewer FTE GPs are less likely to refer their patients for secondary care than larger practices. Single-handed practices are also lesslikely than larger practices to refer patients for treatment by independent sector providers (ISPs). However, there is substantial variation in the quality of care within the same practice size categories. This is particularly true for single-handed practices: despite the significant prevalence of poor performance among single-handed practices, many also provide high-quality care.The relationships between GP practice size and GP behaviour are not necessarily causal. This report controls for differences in the characteristics of the practice population, the local area and the GPs themselves in order to adjust for factors that may impact on both practice size and the indicators we examine. However, a considerable number of unobservable factors remain, such as the underlying health status of the practice populations, and could explain why smaller practices tend to perform differently. This report focuses on GP practice size. There are many other characteristics of GPs that may affect patient outcomes. Further research is required in this area.
Keywords: 330